Brief report: Emotional distress and recent stressful life events in long QT syndrome mutation carriers. (November 2015) - Määttänen, Ilmari; Jokela, Markus; Pulkki-Råback, Laura; Keltikangas-Järvinen, Liisa; Swan, Heikki; Toivonen, Lauri; Merjonen, Päivi; Hintsa, Taina
To study emotional distress in symptomatic and asymptomatic long QT syndrome mutation carriers who had experienced a recent stressful life event. The participants were 209 symptomatic and 279 asymptomatic long QT syndrome mutation carriers. Emotional distress was assessed with the Cope questionnaire and stressful life events with the Social Readjustment Rating Scale. Symptomatic long QT syndrome mutation carriers with burdening recent stressful life events reported a higher emotional distress ( β = 0.35, p < 0.001), while the asymptomatic did not show such difference ( β = 0.13, p = 0.393). Symptomatic long QT syndrome mutation carriers who have experienced stressful life events recently report an increased emotional distress.